HOST-PARASITE GENOMIC INTERACTIONS IN LEISHMANIASIS: EMERGING DIAGNOSTIC BIOMARKERS AND PREDICTIVE GENE SIGNATURES - Abbas, Zainab Khamees; Al Alouci, Muntaha Maddah; Mohsein , Osama A (Journal of Medical Genetics and Clinical Biology, 2026)
Objective: This review aims to explore the genetic underpinnings of Leishmaniasis, focusing on host-parasite genomic interactions and their implications for diagnostics, treatment, and control. Method: The study synthesizes recent advancements in host-parasite genomics, highlighting genetic polymorphisms in the host's immune response and parasite-mediated virulence determinants, identified through high-throughput sequencing and multi-omics analyses. Results: Key findings include the identification of genetic markers associated with immune responses and disease severity, as well as parasite traits influencing tissue tropism and survival. Co-regulated gene networks have been revealed, underscoring the dynamic interplay between host immunity and parasite adaptability. Novelty: The review identifies the potential for genomic biomarkers to differentiate asymptomatic carriers from active cases, predict treatment failure, and enable personalized treatment strategies. Furthermore, it discusses the prospects of genomic insights in developing targeted vaccines and enhancing control programs for leishmaniasis. This work contributes to precision medicine and the future control of leishmaniasis through the application of genomic biomarkers.